QM/MM Investigation of the Role of a Second Coordination Shell Arginine in [NiFe]-Hydrogenases - Escorcia, Andrés M.; Stein, Matthias (Frontiers in Chemistry, 2018)
[NiFe]-hydrogenases are highly efficient catalysts for the heterolytic splitting of molecular hydrogen (H2). The heterobimetallic cysteine-coordinated active site of these enzymes is covered by a highly conserved arginine residue, whose role in the reaction is not fully resolved yet. The structural and catalytic role of this arginine is investigated here using QM/MM calculations with various exchange-correlation functionals. All of them give a very consistent picture of the thermodynamics of H2 oxidation. The concept of the presence of a neutral arginine and its direct involvement as a Frustrated Lewis Pair (FLP) in the reaction is critically evaluated. The arginine, however, would exist in its standard protonation state and perform a critical role in positioning and slightly polarizing the substrate H2. It is not directly involved in the heterolytic processing of H2 but guides its approach and reduces its flexibility during binding. Upon substitution of the positively charged arginine by a charge-conserving lysine residue, the H2 binding position remains unaffected. However, critical hydrogen bonding interactions with nearby aspartate residues are lost. In addition, the H2 polarization is unfavorable and the reduced side-chain volume may negatively affect the kinetics of the catalytic process.